Effect of producer gas staged combustion on the performance and emissions of a single shaft micro-gas turbine running in a dual fuel mode - Sulaiman, S. A. (2017)
Producer gas from biomass gasification has a potential to cover a considerable part of power production in the future, the availability and variety of biomass put it as the fourth energy resource.